Parkon as a treatment of the Parkinson's disease - Golubev VL; Sadekov PA; Pilipovich AA; Goldstein NI (Open Journal of Parkinson's Disease and Treatment - Peertechz Publications, 2019)
The application of the advancements in biophysics and biochemistry in medical science received a new impulse in the recent years. One of them was the discovery of superoxide radicals [1], in the inhaled atmospheric air and the vital role of this radical [2]. New views regarding the vital role of exogenous Reactive Oxygen Species (ROS) were developed [3]. ROS that enter the organism through the inhalation and regulate a series of vital functions receive most of the attention.